Clubfoot treatment in 2015: a global perspective. Issue 4 (3rd September 2018) - Owen, Rosalind M; Capper, Beth; Lavy, Christopher
Abstract : Introduction: Clubfoot affects around 174 000 children born annually, with approximately 90% of these in low-income and middle-income countries (LMIC). Untreated clubfoot causes life-long impairment, affecting individuals' ability to walk and participate in society. The minimally invasive Ponseti treatment is highly effective and has grown in acceptance globally. The objective of this cross-sectional study is to quantify the numbers of countries providing services for clubfoot and children accessing these. Method: In 2015–2016, expected cases of clubfoot were calculated for all countries, using an incidence rate of 1.24/1000 births. Informants were sought from all LMIC, and participants completed a standardised survey about services for clubfoot in their countries in 2015. Data collected were analysed using simple numerical analysis, country coverage levels, trends over time and by income group. Qualitative data were analysed thematically. Results: Responses were received from 55 countries, in which 79% of all expected cases of clubfoot were born. More than 24 000 children with clubfoot were enrolled for Ponseti treatment in 2015. Coverage was less than 25% in the majority of countries. There were higher levels of response and coverage within the lowest income country group. 31 countries reported a national programme for clubfoot, with the majority provided through public–private partnerships. Conclusion: This is the first study to describe global provision of, and access to, treatment services for children with clubfoot. The numbers of children accessing Ponseti treatment for clubfoot in LMIC has risen steadily since 2005. However, coverage remains low, and we estimate that less than 15% of children born with clubfoot in LMIC start treatment. More action to promote the rollout of national clubfoot programmes, build capacity for treatment and enable access and adherence to treatment in order to radically increase coverage and effectiveness is essential and urgent in order to prevent permanent disability caused by clubfoot.